2017
DOI: 10.1111/luts.12152
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Gabapentin in Comparison to Solifenacin Succinate in Adult Overactive Bladder Treatment

Abstract: Gabapentin treatment with acceptable safety profile, improves OAB symptoms and HRQOL domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In experimental fashion, inosine, resiniferatoxin, an E-series prostaglandin 1 receptor antagonist, kynurenine gene transfer via viruses, gamma-aminobutyric acid A and B receptor agonists muscimol and baclofen, a transient receptor potential 1 and a transient receptor potential vanilloid 1 receptor antagonists, an arginase inhibitor, a prostacyclin receptor antagonist, an endothelin-A receptor antagonist, and memantine have been shown to be beneficial [ 24 33 ]. Clinical studies have indicated that mirabegron, tetrahydrocannabinol-cannabidiol oral spray, anticholinergic preparations, and gabapentin are effective in the management of a neurogenic overactive detrusor [ 13 – 18 , 34 , 35 39 ]. However, there is still a group of patients who are unresponsive to the combination of an anticholinergic with the β-adrenergic therapeutic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In experimental fashion, inosine, resiniferatoxin, an E-series prostaglandin 1 receptor antagonist, kynurenine gene transfer via viruses, gamma-aminobutyric acid A and B receptor agonists muscimol and baclofen, a transient receptor potential 1 and a transient receptor potential vanilloid 1 receptor antagonists, an arginase inhibitor, a prostacyclin receptor antagonist, an endothelin-A receptor antagonist, and memantine have been shown to be beneficial [ 24 33 ]. Clinical studies have indicated that mirabegron, tetrahydrocannabinol-cannabidiol oral spray, anticholinergic preparations, and gabapentin are effective in the management of a neurogenic overactive detrusor [ 13 – 18 , 34 , 35 39 ]. However, there is still a group of patients who are unresponsive to the combination of an anticholinergic with the β-adrenergic therapeutic.…”
Section: Discussionmentioning
confidence: 99%
“…With the aim of providing an option to these patients, several molecules have been reported to be successful in an experimental fashion [ 12 ]. Among them, gabapentin, a sodium channel blocker, has also been found to be clinically beneficial in suppressing contractions of the detrusor with an acceptable side effect profile in both adults and children, as well as in neurogenic overactive bladder as in overactive bladder syndrome [ 13 – 18 ]. In this paper we report the results of a single neuro-urology working group that comprises 27 adult patients who did not respond to the combination of an anticholinergic and mirabegron and were treated with add-on gabapentin therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-one RCTs [12][13][14][15][16][17][20][21][22][23][24][25][26][27][28][29][30][31][34][35][36][37][38][39][40][41][42][43][44][45][46] reported urgency episodes/d, containing a total of 13 treatment interventions and a total sample size of 23,764 cases (supplementary Figure 1). The results suggested that SOL5/10mg-QD was signi cantly more effective than other interventions, followed by SOL10mg-QD and SOL5mg-QD.…”
Section: Mean Daily Urgency Episodesmentioning
confidence: 99%
“…Fifty-ve RCTs [11,[13][14][15][17][18][19][20][21][22][23][24][25][26][27][28][30][31][32][33][34][35][36][37][38][40][41][42][43][44][45][46][47][48][49][50][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] reported dry mouth, and to exclude nocebo effect on study outcomes, two articles [11,22]…”
Section: Safety Outcomesmentioning
confidence: 99%
“…10 Gabapentin may inhibit activity of the afferent C-fibers, and then prevent peripheral sensitization. 11 Gabapentin is also effective in neurogenic over-activity, because it can modulate irritability of the sacral reflex center. 12 The combined peripheral and central action of gabapentin may contribute to decrease in the occurrence of CRBD.…”
mentioning
confidence: 99%